Pengaruh Eva dan Roa terhadap MVA pada Perusahaan Sektor Consume Non-Cyclicals yang Terdaftar di Bei Tahun 2019–2023 - Marcella Hardian Wijayanti; Elmira Siska (Jurnal Manajemen Bisnis Digital Terkini, 2025)
This study aims to analyze the effect of Economic Value Added (EVA) and Return on Assets (ROA) on Market Value Added (MVA) in Consumer Non-Cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. This study uses a quantitative approach with multiple linear regression analysis methods. The data used is secondary data obtained from the annual financial statements of six selected companies through the purposive sampling method. The data analysis process includes descriptive statistical tests, classical assumption tests, t tests, F tests, and determination coefficients. The results showed that partially, EVA and ROA had a significant effect on MVA. This is evidenced by the t-calculated value of EVA of 2.322 and ROA of 2.855, both of which are greater than the t-table of 2.04227, and significance values of 0.026 and 0.008, respectively, which are smaller than 0.05. Simultaneously, EVA and ROA also had a significant effect on MVA, as shown by the calculated F value of 6.287 > F table 3.35 and the significance of 0.006 < 0.05. These findings indicate that EVA and ROA are important indicators in explaining a company's market value. This research contributes to investors and company management in understanding the financial factors that affect market added value, as well as as a reference in strategic decision-making based on financial performance.